Transformer design optimization using nested loop / Muhammad Zulkifli Abd Hamid - Muhammad Zulkifli, Abd Hamid (2018)
This paper presents Power Transformer design using Nested Loop by optimizing the important parameters but keeping in sight the guidelines of the International Electro Technical standards and fundamental Power Transformer specification in general. The result obtained by using the Nested Loop optimization have been compared with the result obtained using conventional calculation method (CCM). Using the same sets of parameters, it is evident that the parameters applying the Nested Loop have been optimized in comparison to the parameters in CCM. The result of CCM and Nested Loop have been obtained by coding in MATLAB which is the first effort thus far in the industries in Malaysia. The presented paper provides convenient, accurate, fast and reliable solution to overcome any issues related to the optimization of 132kV Transformer with several listed design options and it fulfills the criteria or compatible with any kinds of Transformer needs by the global grid power system. Hence, this paper demonstrates a better and efficient solution for Power Transformer design using the Nested Loop optimization techniques.